AN ANALYTICAL STUDY OF MARRIAGE ANNULMENT (FASAKH) IN SHĀFIʿĪ JURISPRUDENCE AND ITS IMPLEMENTATION IN THE SYAR'IYAH COURT - Husni Husni; Fauzi Saleh; Agustin Hanapi (PT. Antis International Publisher, 2026)
Objective: Consequently, this research endeavors to deliver a rigorous analysis of fasakh nikah through the theoretical lens of the Shāfiʿī school, coupled with a critical evaluation of its practical enforcement in the Mahkamah Syarʿiyyah. Method:Adopting a library-based research design, the study utilizes content analysis, hermeneutics, and comparative methodologies to scrutinize primary literature, specifically classical Shāfiʿī treatises and contemporary judicial decrees from the Mahkamah Syarʿiyyah. Results: The results indicate that the conceptualization of fasakh in Shāfiʿī doctrine exhibits unique structural characteristics, differentiating it fundamentally from talak (unilateral repudiation), khuluʿ (divorce initiated by the wife), and liʿan (mutual imprecation). The legally recognized bases for annulment categorized into physiological anomalies, statutory barriers, and financial inadequacies are universally anchored in the foundational legal maxim of harm mitigation. Novelty: A comparative evaluation further highlights that the paramount feature of fasakh is its independence from the permissible talak quota and the absence of any requisite financial restitution from the wife, thereby cementing its role as a purely equitable instrument of justice. Its operationalization within the Mahkamah Syarʿiyyah demonstrates a broadening of judicial ijtihad (independent jurisprudential reasoning) capable of adaptively navigating contemporary socio-legal intricacies.